2017
DOI: 10.12681/bgsg.11221
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cretaceous (Maastrichtian) Landvertebrate Diversity in Alba District (Romania)

Abstract: In Romania, Maastrichtian (Late Cretaceous)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Lizards were first recognized in the Romanian uppermost Cretaceous by Grigorescu et al (1985) , and subsequently have been found in most microvertebrate bonebeds from the Haţeg and Transylvanian basins ( Grigorescu et al 1999 ; Codrea et al 2002 , 2010a ; Folie and Codrea 2005 ; Csiki et al 2008 ). In addition, eggshell fragments (probably belonging to squamates) are also common at these sites.…”
Section: The Late Cretaceous Continental Vertebrate Faunas Of Europementioning
confidence: 99%
See 4 more Smart Citations
“…Lizards were first recognized in the Romanian uppermost Cretaceous by Grigorescu et al (1985) , and subsequently have been found in most microvertebrate bonebeds from the Haţeg and Transylvanian basins ( Grigorescu et al 1999 ; Codrea et al 2002 , 2010a ; Folie and Codrea 2005 ; Csiki et al 2008 ). In addition, eggshell fragments (probably belonging to squamates) are also common at these sites.…”
Section: The Late Cretaceous Continental Vertebrate Faunas Of Europementioning
confidence: 99%
“…Hungary: 1 Iharkút and Ajka ( Ősi et al 2012b ). Romania: 1 Rusca Montană Basin ( Vasile and Csiki 2011 ; Codrea et al 2012 ) 2 Haţeg Basin ( Grigorescu 2005 , 2010; Weishampel et al 2010 ) 3 Alba Iulia-Sebeș (southwestern Transylvanian Basin; Codrea et al 2010a , c ; Vremir 2010 ) 4 Borod Basin ( Nopcsa 1902b ) 5 Jibou (northwestern Transylvanian Basin; Codrea and Godefroit 2008 ; Codrea et al 2010c ).…”
Section: The Late Cretaceous Continental Vertebrate Faunas Of Europementioning
confidence: 99%
See 3 more Smart Citations